Polymer-liquid crystal-quantum dot micro-nano composite structure, preparation method and application

By designing the polymer-liquid crystal-quantum dot micro-nano composite structure, the problems of high requirements, complex processes and high costs of quantum dot fluorescence enhancement equipment in the prior art are solved, and stable fluorescence enhancement and cost reduction are achieved.

CN119823503APending Publication Date: 2025-04-15QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311320062.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

When the prior art achieves quantum dot fluorescence enhancement, the equipment requirements are high, the preparation process is complex, the production cost is high, and the extraction light efficiency of the solid-state packaging structure is low.

Method used

A polymer-liquid crystal-quantum dot micro-nano composite structure was designed. In the preparation method, the polymer formed uniformly along the edges of the micro-nano composite structure, and the liquid crystal was self-assembled into a nano-scale layered structure. The quantum dots were embedded in the liquid crystal molecules to form a micro-nano composite structure with a controllable shape.

Benefits of technology

The stable fluorescence enhancement performance is achieved, the preparation method is simplified, the cost is reduced, and the fluorescence of quantum dots is enhanced by multiple scattering, reducing fluorescence leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823503A_ABST
    Figure CN119823503A_ABST
Patent Text Reader

Abstract

The invention provides a polymer-liquid crystal-quantum dot micro-nano composite structure with fluorescence enhancement and a preparation method thereof, and the preparation method comprises the following steps: dissolving a polymer in an organic solution, and then adding liquid crystal and quantum dot dispersion liquid to form a uniform and transparent solution; by means of the large surface energy difference between the super-hydrophobic structured micro-nano structure shape substrate and the super-hydrophilic whole substrate, the uniform transparent solution is subjected to directional induction assembly on the contact surfaces of the two substrates. The polymer forms a uniform array at the edge under the action of the liquid bridge, and drives the flowing liquid crystal to be self-assembled into a nanoscale layered structure, and the quantum dots are embedded into the liquid crystal. Self-assembly of the liquid crystal is driven by means of orientation of the edge polymer, the liquid crystal is forced to be separated out of the polymer, the content of the liquid crystal is lower than 20%, the fusion point of the polymer is not affected, the structural shape of a fluorescence enhancement device can be kept, and the problems that in the existing fluorescence technology, light loss is large, control is not easy, the process is complex, cost is high, and cost is low are solved. And structuring is difficult.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of functional composite materials and quantum dot fluorescence technology, and in particular to a fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure, a preparation method and application thereof. Background Art

[0002] As one of the most important members of nanomaterials, quantum dots are one of the new nanomaterials with the most development potential in recent years. They are zero-dimensional fluorescent semiconductor nanoparticles. The principle of semiconductor quantum dots emitting fluorescence is that when the semiconductor material is irradiated by laser, it absorbs photons, and the electrons in the valence band transition to the conduction band. The electrons in the conduction band can also transition back to the valence band and emit photons, thereby generating fluorescence. Semiconductor quantum dots have the characteristics of wide and continuous excitation spectrum, narrow and symmetrical emission spectrum, high and stable luminescence efficiency, adjustable emission light color, high fluorescence quantum yield, stable fluorescence, and long luminescence life. They not only have their own characteristics but also make up for the shortcomings of traditional fluorescent materials. They have broad application prospects in the fields of biosensing, optoelectronic devices, fluorescence imaging, liquid crystal display, etc. Among them, fluorescence intensity is an important parameter for evaluating the performance of quantum dot optoelectronic devices. At present, quantum dot fluorescence enhancement can adopt technologies such as photonic crystals, localized interface plasma resonance, metal fluorescence enhancement, and dielectric fluorescence enhancement. Although the above technologies can achieve significant enhancement of quantum dot fluorescence intensity, they have high equipment requirements, complex preparation processes, and high production costs. The luminous efficiency of quantum dots is limited by the difficulty of encapsulation with surface thin film technology or the low light extraction efficiency of solid-state encapsulation structure.

[0003] Most research on polymer / liquid crystal / quantum dot fluorescent devices focuses on polymer dispersed liquid crystal (PDLC) technology.

[0004] PDLC is a composite material in which liquid crystal droplets are evenly dispersed in a continuous polymer network. The liquid crystal droplets are rearranged by heating or electric field to enhance fluorescence. In this method, liquid crystal precipitates from the polymer and phase separation occurs, which is the basis of PDLC devices. Whether it is phase separation caused by solvent evaporation or phase separation caused by polymerization, the weight ratio of liquid crystal to polymer must be higher than 2:3. The high proportion of liquid crystal content in the polymer network causes the polymer glass temperature to decrease, resulting in the collapse of the morphology of the PDLC device, so most PDLCs are poured into liquid crystal boxes to maintain their inherent form.

[0005] Therefore, in order to realize fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nanostructures, it is necessary to seek new structures and preparation methods. Summary of the invention

[0006] The technical problem to be solved by the present disclosure is to design a new preparation method for a polymer-liquid crystal-quantum dot micro-nano composite structure in view of the deficiencies in the above-mentioned prior art.

[0007] The technical solution adopted in this disclosure is: A fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure, the micro-nano composite structure has a controllable shape, the polymer forms a uniform arrangement along the edge of the micro-nano composite structure, based on the uniform arrangement, the liquid crystal self-assembles into a nano-level layered structure along the edge of the micro-nano composite structure, and the quantum dots are embedded in the liquid crystal molecules, wherein the concentration of the polymer is 0.5-50 mg / ml, the liquid crystal accounts for 5-20% of the weight of the polymer, and the quantum dots account for 0-10% of the weight of the liquid crystal.

[0008] Optionally, the polymer includes PS or PMMA.

[0009] Optionally, the liquid crystal includes 5CB, 7CB, 8CB or E7.

[0010] Optionally, the quantum dots include CdSe / ZnS or CsPbX3.

[0011] Optionally, the shape of the micro-nano composite structure includes a ring shape or a strip shape.

[0012] The present disclosure also provides a method for preparing a fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure, comprising the following steps: According to the shape of the micro-nano structure to be prepared, preparing the micro-nano structure shape template; Super-hydrophobic modification of the micro-nano structure shape template; Prepare the polymer-liquid crystal-quantum dot dispersion in proportion; Selecting an upper substrate and modifying the upper substrate to be superhydrophilic; Dropping the polymer-liquid crystal-quantum dot dispersion between the upper substrate and the micro-nano structure shape template; Directed self-assembly of the polymer-liquid crystal-quantum dot micro-nano structure.

[0013] Optionally, the preparation of the micro-nano structure shape template includes etching a silicon wafer to form a ring array silicon column template or a strip silicon column array.

[0014] Optionally, the dispersion liquid uses chlorobenzene or THF as solvent.

[0015] Optionally, the polymer includes PS or PMMA; and / or the liquid crystal includes 5CB, 7CB, 8CB or E7; and / or the quantum dots include CdSe / ZnS or CsPbX3; and / or the upper substrate includes an ITO glass slide.

[0016] The present disclosure also proposes a fluorescence enhancement application, using the fluorescence enhanced polymer-liquid crystal-quantum dot micro-nano composite structure proposed in the present disclosure.

[0017] Optionally, the fluorescence enhancement application includes display or fluorescence anti-counterfeiting.

[0018] Compared with the prior art, the present invention has the following advantages: (1) The present disclosure provides a fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure, which has a controllable shape, a stable morphology, and excellent fluorescence enhancement performance.

[0019] (2) The present disclosure provides a method for preparing a fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure. The preparation method is simple and low-cost. The pattern of the photolithography plate can be adjusted according to the different needs of actual applications to change the pattern of the silicon substrate to meet the application of different fluorescence enhancement patterns.

[0020] (3) The present disclosure provides a fluorescence-enhanced polymer / liquid crystal / quantum dot micro-nano composite structure. When used as a fluorescence application, when the quantum dots are irradiated with excitation light, the fluorescence emitted by the quantum dots is scattered in multiple ways in the nanostructures of the polymer and liquid crystal. After multiple scattering, the excitation light and the fluorescence form an enhanced field while reducing leakage. These two processes work together to enhance the fluorescence of the quantum dots, thereby achieving fluorescence enhancement of the micro-nano composite structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 FIG. 4 is a scanning electron microscope image of an annular silicon pillar in one embodiment of the present disclosure.

[0022] Figure 2 These are an optical micrograph, a polarizing micrograph, and a polarizing micrograph with a light compensation plate inserted of an oriented PMMA-5CB-CdSe / ZnS quantum dot composite in one embodiment of the present disclosure.

[0023] Figure 3 This is a comparison diagram of an optical microscope image and a fluorescence microscope image of an oriented PMMA-5CB-CdSe / ZnS quantum dot composite in one embodiment of the present disclosure.

[0024] Figure 4 This is a schematic diagram of the oriented PMMA-5CB-CdSe / ZnS quantum dot micro-nano composite structure in one embodiment of the present disclosure.

[0025] Figure 5A comparison chart of the fluorescence intensity of the oriented PMMA-5CB-CdSe / ZnS quantum dot composite and the fluorescence intensity of PMMA-5CB and PMMA-CdSe / ZnS in one embodiment of the present disclosure. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0027] By referring to the following detailed description of exemplary embodiments and the accompanying drawings, the present disclosure and the method for implementing the present disclosure can be better understood. However, the present disclosure can be implemented in many different forms and should not be construed as being limited to the exemplary embodiments set forth herein. The same reference numerals may always refer to the same elements. In the accompanying drawings, the thickness of layers and regions may be exaggerated for clarity.

[0028] In order to make the purpose, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are not intended to limit the present disclosure. In addition, the technical features involved in each embodiment of the present disclosure described below can be combined with each other as long as they do not conflict with each other.

[0029] Example 1 like Figure 1-5 As shown, this embodiment proposes a polymer-liquid crystal-quantum dot micro-nano composite structure with fluorescence enhancement, in which: the micro-nano composite structure has a controllable shape, the polymer forms a uniform arrangement along the edge of the micro-nano composite structure, based on the uniform arrangement, the liquid crystal self-assembles into a nano-scale layered structure along the edge of the micro-nano composite structure, and the quantum dots are embedded in the liquid crystal, wherein the concentration of the polymer is 0.5-50 mg / mL, the liquid crystal accounts for 5-20% of the weight of the polymer, and the quantum dots account for 0-10% of the weight of the liquid crystal.

[0030] Specifically, the polymer may be PS or PMMA; and the liquid crystal may be 5CB, 7CB, 8CB or E7.

[0031] Wherein, the quantum dots include CdSe / ZnS or CsPbX3.

[0032] Specifically, the shape of the micro-nano composite structure can be set as needed. In the present embodiment, the shape of the micro-nano composite structure is, for example, a ring or a strip.

[0033] In this embodiment, the liquid crystal accounts for 5%-20% of the weight of the polymer. When the liquid crystal accounts for less than 5% of the weight of the polymer, the amount of liquid crystal is too small to completely fill the gaps in the regularly arranged polymers. When quantum dots are added, it is not conducive to reducing fluorescence leakage and enhancing excited fluorescence.

[0034] When the ratio of liquid crystal to polymer is greater than 20%, the amount of liquid crystal is too much and the gap space between the regularly arranged polymers is too small to bind so many liquid crystals, resulting in liquid crystal overflow and waste of materials. At the same time, the overflowing liquid crystal will take away the quantum dots in the composite structure, reducing the enhancement of fluorescence.

[0035] For quantum dots, when the weight of quantum dots in liquid crystal is higher than 10%, the amount of quantum dots is too large and fills the gap between the entire polymer and liquid crystal, affecting the arrangement of the polymer and liquid crystal, and finally affecting the enhancement of quantum dot fluorescence.

[0036] Compared to polymer dispersed liquid crystal (PDLC) technology, PDLC is a composite material in which liquid crystal droplets are uniformly dispersed in a continuous polymer network. The droplets of liquid crystal are rearranged by heating or electric field to enhance fluorescence. In this method, liquid crystal precipitates from the polymer, and phase separation is the basis of PDLC devices. Whether it is phase separation caused by solvent evaporation or phase separation caused by polymerization, the weight ratio of liquid crystal to polymer must be higher than 2:3. The high proportion of liquid crystal content in the polymer network causes the glass temperature of the polymer to decrease, resulting in the collapse of the morphology of the PDLC device, so most PDLCs are poured into liquid crystal boxes to maintain their inherent morphology.

[0037] The working principle of the polymer-liquid crystal-quantum dot device proposed in this embodiment is very different from the traditional PDLC principle. Under the induction of wettability and the action of solvent volatilization, the polymer begins to orient on the outside of the top of the template (such as silicon pillar). The orientation of the polymer causes the liquid crystal molecules to deflect, and the liquid crystal self-assembles into a nano-level layered structure. In order to enhance fluorescence, quantum dots can be added. When quantum dots are added to the polymer / liquid crystal, the arrangement of the flowing liquid crystal drives the movement of the quantum dots and embeds them between the liquid crystal molecules. The polymer-liquid crystal-quantum dot micro-nano composite structure is formed as shown in FIG. Figure 4 shown.

[0038] In this embodiment, since the precipitation of liquid crystal is driven by the orientation of the edge polymer of the micro-nano composite structure to drive the self-assembly of liquid crystal, forcing the liquid crystal to precipitate from the polymer, the liquid crystal content can be less than 20%; at the same time, the liquid crystal content below 20% does not affect the melting point of the polymer, which is beneficial to maintaining the structural shape of the fluorescence enhancement device, which is different from the traditional polymer dispersed liquid crystal. In the traditional mode: the ratio of liquid crystal to polymer is higher than 2:3, and the liquid crystal can be precipitated from the polymer network.

[0039] In this way, the use of a high proportion of liquid crystal is avoided, and a stable polymer-liquid crystal-quantum dot micro-nano composite structure can be obtained.

[0040] Secondly, when liquid liquid crystals are arranged in polymers, they are uniformly oriented and embedded in the polymers, which drives the uniform distribution of quantum dots without the need for additional external fields, greatly improving the luminous efficiency of quantum dots.

[0041] Example 2 This embodiment provides a method for preparing the fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure of embodiment 1. Specifically, the preparation method of the micro-nano composite structure includes the following steps: According to the shape of the micro-nano structure to be prepared, preparing the micro-nano structure shape template; Super-hydrophobic modification of the micro-nano structure shape template; Prepare the polymer-liquid crystal-quantum dot dispersion in proportion; Selecting an upper substrate and modifying the upper substrate to be superhydrophilic; Dropping the polymer-liquid crystal-quantum dot dispersion between the upper substrate and the micro-nano structure shape template; Directed self-assembly of the polymer-liquid crystal-quantum dot micro-nano structure.

[0042] The shape template for preparing the micro-nano structure is formed by, for example, etching a silicon wafer.

[0043] For example, nitrogen-doped <100> A SiO2 / Si silicon wafer with a crystal surface, a diameter of 5 inches and a thickness of 525 microns is coated with photoresist according to the semiconductor photolithography process. A pre-designed chrome (Cr)-plated quartz photomask is used to irradiate the photoresist through a laser direct writing device to solidify it. After post-baking and development, the unexposed part of the silicon wafer surface is exposed. The silicon wafer with the photoresist pattern is deep reactive ion etched for about 6 minutes using a fluorine-based reagent. Finally, the substrate is debonded and cleaned with acetone and ethanol. The obtained circular ring array silicon column template has an inner and outer diameter of 15 microns and 25 microns respectively, a height of 20 microns, and a center distance of 50 microns between the patterns; Figure 1 shown.

[0044] The shape template of the micro-nano structure can be prepared as needed, for example, it can also be a strip silicon column with a length of 1 cm, a width of 5 microns, and a spacing of 8 microns.

[0045] The super-hydrophobic modification of the micro-nano structure shape template may be performed, for example, by the following steps: The micro-nano structured template, such as the annular silicon column template, is cleaned with ethanol and acetone. The template is treated with a low-temperature plasma treatment apparatus (oxygen atmosphere, discharge power of 200W, treatment time of 300s) to activate its surface, and then placed in a vacuum oven, 5μl of fluorosilane is dropped, vacuum environment, temperature of 80℃, and placed for 12 hours to obtain a super-hydrophobic annular structured silicon column template, and the water contact angle can reach about 150°.

[0046] The polymer-liquid crystal-quantum dot dispersion is configured in proportion, for example: wherein PMMA is selected as the polymer, PMMA is dissolved in chlorobenzene by a magnetic stirrer, and a certain amount of liquid crystal and quantum dot dispersion is added to the chlorobenzene solution of PMMA, and the PMMA concentration is 20 mg / mL, and the mass ratio of PMMA: liquid crystal: quantum dots is, for example, 5:0.25-1:0.0125-0.05. For example, the mass ratio of PMMA: liquid crystal: quantum dots is, for example, 5:0.25:0.0125, or 5:0.5:0.03, or 5:1:0.02, and the amount of liquid crystal and quantum dots added satisfies the following relationship: the liquid crystal accounts for 5-20% of the weight of the polymer, and the quantum dots account for 0-10% of the weight of the liquid crystal. Wherein, the liquid crystal is, for example, 5CB, and the quantum dots are, for example, CdSe / ZnS.

[0047] Select an upper substrate and super-hydrophilically modify the upper substrate, for example, by the following steps: The upper substrate is, for example, an ITO glass slide, and a low-temperature plasma treatment apparatus (oxygen atmosphere, discharge power of 200 W, treatment time of 300 s) is used. After treatment, the ITO glass slide becomes super-hydrophilic, and the water contact angle is 0°.

[0048] The polymer-liquid crystal-quantum dot dispersion is dripped between the upper substrate and the micro-nano structure shape template; and the polymer-liquid crystal-quantum dot micro-nano structure is self-assembled in a directional manner. For example, the steps include: Take 10 μl of PMMA-5CB-CdSe / ZnS quantum dot chlorobenzene solution and drop it between the superhydrophobic annular silicon column template and the superhydrophilic ITO glass slide to form a "sandwich" structure. The lower substrate is a superhydrophobic annular silicon column template, the upper substrate is a superhydrophilic ITO glass, and the middle is the PMMA-5CB-CdSe / ZnS quantum dot chlorobenzene solution. Due to the large surface energy difference between the silicon substrate and the superhydrophilic leveling substrate, the mixed uniform solution forms a micrometer-scale liquid bridge on the contact surface of the two substrates to induce the PMMA-5CB-CdSe / ZnS quantum dots to be assembled in a directional manner. Under the action of the liquid bridge, the polymer forms a uniform arrangement at the edge of the micro-nano structure shape template, driving the flowing liquid crystal to self-assemble into a nanometer-scale layered structure and embed the quantum dots into the liquid crystal. At the same time, due to the anchoring effect of the silicon substrate, a micro-nano composite structure of the same shape as the silicon substrate is formed on the upper substrate. Figure 2 Figure 3 , Figure 4 As shown. Among them, Figure 2 This is a schematic diagram of a microscopic image of the polymer-liquid crystal-quantum dot ring after orientation. Figure 2 (a) Schematic diagram of optical image; Figure 2 (b) is a schematic diagram of the polarization image when the micron ring is at 45° to the polarizer; Figure 2 (c) Schematic diagram of polarized light image with a light compensation plate inserted in the micron ring.

[0049] Figure 3 This is a comparison of the optical microscope image and the fluorescence microscope image of the PMMA-5CB-CdSe / ZnS quantum dot composite after orientation. Figure 3 (a) is an optical picture; Figure 3 (b) is the fluorescence image.

[0050] Figure 4 Schematic diagram of the structure of the polymer-liquid crystal-quantum dot micro-nano composite structure prepared in this embodiment, wherein Figure 4 (a) is a schematic diagram of the micro-nanostructure shape template. Figure 4 (b) is a schematic diagram of the polymer-liquid crystal-quantum dot micro-nano composite structure.

[0051] Those skilled in the art can understand that: the polymer applicable to this embodiment also includes PS; the liquid crystal also includes 7CB, 8CB or E7; the quantum dot also includes CsPbX3; and the organic solvent also includes THF.

[0052] Example 3 This embodiment proposes a fluorescence enhancement application of the fluorescence enhanced polymer-liquid crystal-quantum dot micro-nano composite structure of embodiment 1.

[0053] When the incident light acts as excitation light through the oriented PMMA-5CB-CdSe / ZnS quantum dot composite micropattern, it excites the CdSe / ZnS quantum dots to emit fluorescence. The fluorescence emitted by the CdSe / ZnS quantum dots is repeatedly scattered in the nanostructure of PMMA and 5CB. The excitation light and fluorescence form an enhanced field after multiple scattering, while reducing leakage. These two processes work together to enhance the fluorescence of the CdSe / ZnS quantum dots, thereby achieving fluorescence enhancement of the micro-nano composite structure. The fluorescence spectra of the oriented micro-nano composite structures of different polymer composites are shown in Figure 2. Figure 4 As shown, it can be seen that the PMMA-5CB-CdSe / ZnS quantum dot composite micro-nano composite structure prepared in the present invention effectively achieves fluorescence enhancement.

[0054] The polymer-liquid crystal-quantum dot micro-nano composite structure proposed in the present disclosure can be applied to the display field or the fluorescent anti-counterfeiting field.

[0055] Compared with the prior art, the present invention has the following advantages: (1) The present disclosure provides a fluorescence-enhanced polymer / liquid crystal / quantum dot micro-nano composite structure, which has a stable structure and morphology, as well as excellent fluorescence enhancement performance compared to the prior art.

[0056] (2) The present disclosure provides a method for preparing a fluorescence-enhanced polymer / liquid crystal / quantum dot micro-nano composite structure, which has the advantages of simple preparation method, low cost and high stability.

[0057] (3) The present disclosure provides a method for preparing a fluorescence-enhanced polymer / liquid crystal / quantum dot micro-nano composite structure. According to different needs of practical applications, the pattern of the photolithography plate can be adjusted to change the pattern of the silicon substrate to meet the application of different fluorescence-enhanced patterns.

[0058] (4) The present disclosure provides a method for preparing a fluorescence-enhanced polymer / liquid crystal / quantum dot micro-nano composite structure. When the quantum dots are irradiated with excitation light, the fluorescence emitted by the quantum dots is scattered in multiple ways in the nanostructures of the polymer and the liquid crystal. The excitation light and the fluorescence form an enhanced field after multiple scattering, while reducing leakage. These two processes work together to enhance the fluorescence of the quantum dots, thereby achieving fluorescence enhancement of the micro-nano composite structure.

[0059] The above-described embodiments are only descriptions of the preferred implementation methods of the present disclosure, and the preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Without departing from the design spirit of the present disclosure, various modifications and improvements made by ordinary technicians in this field to the technical solution of the present disclosure should fall within the protection scope determined by the claims of the present disclosure.

Claims

1. A fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure, characterized in that: The micro-nano composite structure has a controllable shape, and the polymer forms a uniform arrangement along the edge of the micro-nano composite structure. Based on the uniform arrangement, the liquid crystal self-assembles into a nano-level layered structure along the edge of the micro-nano composite structure, and the quantum dots are embedded in the liquid crystal molecules; wherein the concentration of the polymer is 0.5-50 mg / ml, the liquid crystal accounts for 5-20% of the weight of the polymer, and the quantum dots account for 0-10% of the weight of the liquid crystal.

2. The fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure according to claim 1, characterized in that: The polymer includes PS or PMMA.

3. The fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure according to claim 1 or 2, characterized in that: The liquid crystal includes 5CB, 7CB, 8CB or E7.

4. The fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure according to claim 1 or 2, characterized in that: The quantum dots include CdSe / ZnS or CsPbX3.

5. The fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure according to claim 1, characterized in that: The shape of the micro-nano composite structure includes a ring shape or a strip shape.

6. A method for preparing the fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure according to claim 1, characterized in that: The following steps are involved: According to the shape of the micro-nano composite structure to be prepared, preparing the micro-nano composite structure shape template; Super-hydrophobic modification of the micro-nano composite structure shape template; Prepare the polymer-liquid crystal-quantum dot dispersion in proportion; Selecting an upper substrate and modifying the upper substrate to be superhydrophilic; Dropping the polymer-liquid crystal-quantum dot dispersion between the upper substrate and the micro-nano composite structure shape template; Directed self-assembly of the polymer-liquid crystal-quantum dot micro-nano composite structure.

7. The method according to claim 6, characterized in that The preparation of the micro-nano composite structure shape template includes etching a silicon wafer to form a ring array silicon column template or a strip silicon column array.

8. The method according to claim 6, characterized in that The dispersion liquid uses chlorobenzene or THF as a solvent.

9. The method according to claim 6, characterized in that The polymer includes PS or PMMA; and / or the liquid crystal includes 5CB, 7CB, 8CB or E7; and / or the quantum dots include CdSe / ZnS or CsPbX3; and / or the upper substrate includes an ITO glass slide.

10. A fluorescence enhancement application, characterized in that: A fluorescence-enhanced polymer-liquid crystal-quantum dot micro-nano composite structure is used as described in any one of claims 1 to 5.